Impact of tobacco control policies on cigarette consumption in Malaysia - Mohamed Nor, Norashidah; Kher, Wency Thinng Bui; Abd. Ghani, Judhiana; Hassan, Noraryana; Baharom, Nizam (Universiti Malaysia Sarawak, 2022)
Raising the cigarettes price is an important measure to reduce the consumption of cigarettes and smoking rate. Besides price, other measures of tobacco control policies also play essential roles in determining the demand for cigarettes in Malaysia. In this study, the impact of tobacco control policies on consumption of cigarettes was examined using the fully modified ordinary least squares (FMOLS) technique. The study found that higher cigarettes price due to excise tax significantly decreased consumption of cigarette in the long run. An increase of 10% in the price of cigarettes reduces 7.69% of its consumption. Other measures of tobacco control policies except the “Tak Nak” campaign were also found to have reduced the consumption of cigarette significantly. The study concludes that the effective ways of reducing the use of cigarettes are by increasing the cigarette tax and strengthening the enforcement of other tobacco policies measures.